DOES SHARIAH FINTECH CARRIES MORE ETHICAL IMPACTS THAN SHARIAH BANKS: GLOBAL INDEX ANALYSIS ON INDONESIAN INDUSTRY - Bin-Armia, Muhammad Syauqi (Jihbiz: Global Journal of Islamic Banking and Finance, 2024)
This article provides an analysis of Indonesia’s Shariah Fintech industry’s ethical impacts agaisnt Shariah banks, particularly from a global index point of view. The Shariah fintech industry experienced enormous development, particularly in the post-pandemic era with a holistic impact socially and ethically. Meanwhile, the Sharia banking industry did not have sufficient impacts on society. Does this mean that Shariah fintech has more ethical impacts and received wider acceptance, particularly those are categorised as unbanked and underbanked entrepreneurs?  Hence, the study will be qualitatively analysed using the global index approach in order to find the result. The research adopted the library research approach and used the published and research articles as secondary data alongside the analysis. The study concluded that Shariah fintech successfully contributed ethically to society, particularly for those who were grouped as unbanked categories. Shariah banks should hands-in-hand with the Shariah fintech to create a more impactful business ecosystem and meaningful collaboration with marginalised enterprises.